ANALISIS DISTRIBUSI DAN KUALIFIKASI GURU PENDIDIKAN AGAMA ISLAM (Implikasinya terhadap Peningkatan Mutu Pendidikan di Kabupaten Sampang) - Muslim, Buhori (Jurnal Ilmiah Ibtida, 2024)
This study aims to analyze the distribution and qualifications of Islamic Religious Education (PAI) teachers in Sampang District, Indonesia. Using a quantitative approach, this study analyzes secondary data from the Sampang District Statistics Agency report with a focus on the variables of gender, employment status, education level, and teacher certification status. The results showed a moderate gender imbalance (55.1% male, 44.9% female) and the dominance of non-civil servant teachers (65.7%). The majority of teachers (88.7%) have met the minimum qualification of S1, but the percentage of S2 is still low (6%). Statistical analysis revealed a significant relationship between gender and certification status, differences in education level between PNS and non-civil servant teachers, and a negative correlation between education level and certification status. These findings indicate the need for more inclusive and gender-equitable policies in teacher professional development, increased opportunities for non-civil servant teachers, and a thorough evaluation of the certification process to improve the quality of Islamic religious education in Indonesia.